The Social and the Psychological Problems of Young Families - Matulienė, Gražina; Dobrovolskienė, Ramunė (Sociologija. Mintis ir veiksmas, 2002)
The social psychological point of view to the family, its formation and development was used as the theoretical background of the paper. The task of the paper was to analyse the attitudes of all the respondence, the women and the men separately towards the family, the conditions of a couple becoming a family and the families functioning under the contemporary social economic circumstances. For the above mentioned purpose serve the data of special research of the couple’s who decided to be married as well as the data of other investigators. The method of investigation: the special questionnaire for the couple’s, who arrived to register the marriage was prepared. Results: the differences towards the attitudes to the joint house-hold between the persons who lived together before the marriage and did not lived together were revealed. It was not proved the opinion about the fact that life together before the marriage helps to prepare for the domestic affairs. The psychological atmosphere of the spouses show a tendency for a social interaction combining the family and the career problems also looking for a joint decisions in a case of the controversy. Conclusions: the different view of the women and the men in assessing the family problems guid to the necessity to change the family police from the patriarchal to the egalitarian.
Keywords: becoming a family; unmarried partner relationship; social roles; psychological athmosphere in the family